2019
DOI: 10.1002/cjce.23460
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of coalescence behaviour of bubble pairs forming at capillary orifices submerged in bacterial suspension

Abstract: Coalescence behaviour of bubble pairs markedly affected methane bioconversion because methane is usually pumped into a bacterial suspension through an aeration system, forming bubbles at capillary orifices. In the present work, a bioreactor was developed to observe the coalescence behaviour of bubble pairs forming at capillary orifices submerged in bacterial suspension via a visualization experiment. The results indicated that in a bacterial suspension the inrush bubble number decreased and the inrush time sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In the absence of air injection, the bubble oscillation is driven by excess energy due to the reduction in the bubble's surface area and curvature. [10,19] The projection area (A) provides further insight into the flowrate effects on the post-coalescence oscillatory behaviours of the coalesced bubble.…”
Section: Post-coalescence Oscillatory Behavioursmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of air injection, the bubble oscillation is driven by excess energy due to the reduction in the bubble's surface area and curvature. [10,19] The projection area (A) provides further insight into the flowrate effects on the post-coalescence oscillatory behaviours of the coalesced bubble.…”
Section: Post-coalescence Oscillatory Behavioursmentioning
confidence: 99%
“…They also observed a decrease in coalescence time with increasing flowrate. Guo et al [ 10 ] investigated the coalescence behaviours of two bubbles at capillaries in bacterial suspension and water. They reported that the ratio of bubble width and height ( W / H ) before coalescence fluctuates more prominently at high flowrates, whereas no significant difference in W / H after coalescence was observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bubble is widespread in various industrial fields, such as refrigeration, sewage treatment, renewable energy, and national defence, [1][2][3][4] where its dynamic behaviour directly affects the mass transfer performance of the equipment and even its safety. [5][6][7][8] In general, bubble formation is influenced by many factors, including fluid physical property, [9][10][11][12] gas escaping hole characteristic, [13][14][15][16] gas flow rate, [17][18][19] liquid flow rate, [20][21][22] and so on, which is a complicated, non-linear, asymmetrical, and unstable process. [23][24][25] Therefore, it is of great theoretical significance to study the dynamic behaviour of bubble.…”
Section: Introductionmentioning
confidence: 99%